PELATIHAN PERANCANGAN DESAIN KEMASAN BERBASIS KOMIK LITERASI PADA BUMNAG SAIYO SAKATO, KECAMATAN LUBUK ALUNG, KABUPATEN PADANG PARIAMAN - Fithri, Prima; Wisnel, Wisnel; Kesogihan, R. Sultan Fauzi; Wahyuni, Nadya Sri; Aufar, Abi Rafdi (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
Literacy comic-based packaging for micro, small, and medium enterprises (MSMEs) in Nagari Sikabu Bukik, Lubuk Alung, Padang Pariaman, West Sumatra, was developed to overcome the low competitiveness of local products due to unattractive and uninformative packaging designs. The main problem faced is the lack of skills in designing effective packaging to increase the selling value and strengthen the brand identity of local products. The purpose of this activity is to increase the capacity of MSMEs, especially those incorporated in the Saiyo Sakato Village-Owned Enterprise (BUMNag), in designing attractive, educational, and competitive product packaging. This activity involved 46 participants, including BUMNag administrators and MSMEs engaged in local food production, such as cookies and traditional foods. The methods used included socialization, tutorials on literacy comic-based packaging design techniques, and hands-on practice sessions using the Canva Pro platform. The training began with an explanation of the concept of literacy comic-based packaging design, continued with technical guidance on making designs, and ended with independent practice by participants. The results of the activity showed an increase in participants' skills in creating innovative and functional packaging. This literacy comic-based packaging is not only visually appealing but also able to convey educational messages to consumers. In addition, the handover of Canva Pro access to Nagari Sikabu Bukik is a sustainable step to support independent design development. Training in designing literacy comic-based packaging designs has succeeded in improving the quality of MSME product packaging, strengthening brand identity, and expanding the marketing potential of local products.